APPLICATION OF THE MAKE A MATCH METHOD TO INCREASE THE SCIENCE LEARNING MOTIVATION OF ELEMENTARY SCHOOL STUDENTS - Azizah Thalib; Aisha Rachma Andini (Universitas Tadulako, 2021)
The purpose of this study was to increase students' learning motivation through the make a match method in science subjects in class V SD Negeri Sengare 03, Talun District, Pekalongan Regency. The type of research used is classroom action research from Kemmis and Mc. Taggart. The research subjects were 17 students. Data collection techniques are non-test techniques (questionnaires and observation). Data analysis used qualitative analysis techniques. Qualitative data analysis to analyze student learning motivation and teacher skills. The results showed that the use of the make a match method could increase students' motivation to learn science. Obtained classical completeness after the implementation of the first cycle increased to 64.70%, the implementation of the second cycle increased to 82.35%, and the implementation of the third cycle increased to 94.12%. So from the implementation of the first cycle to the implementation of the third cycle increased by 29.42%. So it can be concluded that the application of the make a match method can increase student learning motivation.